The economic impact of recession announcements - Eggers, AC; Ellison, M; Lee, SS (Elsevier, 2021)
The convention in the news media is to announce a recession if a country experiences two consecutive quarters of negative growth. We exploit the arbitrary threshold implied by this practice to identify the economic impact of recession announcements through a Regression Discontinuity Design (RDD). Estimation results show that news of a recession leads to a discontinuous fall in consumer confidence, consumption growth and final estimates of GDP growth in a panel of countries. The effect is large, robust and statistically significant.